Sympathetic nervous system-targeted neuropeptide Y overexpression in mice enhances neointimal formation in response to vascular injury - Ruohonen, Suvi T. (2008)
Sympathetic neurotransmitter neuropeptide Y (NPY) is associated with vascular remodelling, neointimal hyperplasia and atherosclerosis in experimental animal models and clinical studies. In order to study the role of sympathetic nerve-produced NPY in vascular diseases, transgenic mouse model overexpressing NPY in central and peripheral noradrenergic neurons under the dopamine-beta-hydroxylase (DBH) promoter was recently created (OE-NPY(DBH) mouse). This study aimed to examine the effect of NPY overexpression on arterial neointimal hyperplasia in an experimental model of vascular injury. Transgenic OE-NPY(DBH) mice and wildtype control mice of two different inbred strains (C57BL/6 and FVB/n) underwent a femoral artery surgery with a transluminar injury by a 0.38-mm guide wire insertion. Arteries were harvested 4 weeks from the surgery, and they were stained for basic morphology. Both strains of OE-NPY(DBH) mice, as compared with wildtype control mice, showed on average 50% greater formation of the neointima (P < 0.01) and an increase in the medial area (P = 0.05). The results suggest that moderately increased neuronal NPY causes the arteries to be more susceptible to femoral artery thickening after endothelial injury. The OE-NPY(DBH) mouse provides a novel tool to explore the role of NPY in the development of vascular disease related to metabolic disorders.